CXC chemokines and antimicrobial peptides in rhinovirus‐induced experimental asthma exacerbations. Issue 7 (July 2014) - Rohde, G.; Message, S. D.; Haas, J. J.; Kebadze, T.; Parker, H.; Laza‐Stanca, V.; Khaitov, M. R.; Kon, O. M.; Stanciu, L. A.; Mallia, P.; Edwards, M. R.; Johnston, S. L.
Summary Rationale Rhinoviruses (RVs) are the major triggers of asthma exacerbations. We have shown previously that lower respiratory tract symptoms, airflow obstruction, and neutrophilic airway inflammation were increased in experimental RV‐induced asthma exacerbations. Objectives We hypothesized that neutrophil‐related CXC chemokines and antimicrobial peptides are increased and related to clinical, virologic, and pathologic outcomes in RV‐induced exacerbations of asthma. Methods Protein levels of antimicrobial peptides (SLPI, HNP 1–3, elafin, and LL‐37) and neutrophil chemokines (CXCL1/GRO‐α, CXCL2/GRO‐β, CXCL5/ENA‐78, CXCL6/GCP‐2, CXCL7/NAP‐2, and CXCL8/IL‐8) were determined in bronchoalveolar lavage (BAL) fluid of 10 asthmatics and 15 normal controls taken before, at day four during and 6 weeks post‐experimental infection. Results BAL HNP 1–3 and Elafin were higher, CXCL7/NAP‐2 was lower in asthmatics compared with controls at day 4 (P = 0.035, P = 0.048, and P = 0.025, respectively). BAL HNP 1–3 and CXCL8/IL‐8 were increased during infection (P = 0.003 and P = 0.011, respectively). There was a trend to increased BAL neutrophils at day 4 compared with baseline (P = 0.076). BAL HNP 1–3 was positively correlated with BAL neutrophil numbers at day 4. There were no correlations between clinical parameters and HNP1–3 or IL‐8 levels. Conclusions We propose that RV infection in asthma leads to increased release of CXCL8/IL‐8, attracting neutrophils into the airways where they release HNP 1–3, which further enhances airway neutrophilia. Strategies to inhibit CXCL8/IL‐8 may be useful in treatment of virus‐induced asthma exacerbations.